The Shaft Tomb of Menekhibnekau at Abusir Season of 2008 - Bareš, Ladislav (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
During the autumn season of 2008, the epigraphic work and photographic documentation of the relief decoration in the burial chamber of Menekhibnekau (uncovered in April 2007) continued, together with the cleaning and conservation of its side walls. In cleaning the surface layers of sand on the eastern and southern sides of the main shaft, a number of items have been found, among them numerous fragments of a large basalt statue of a walking cow (representing the goddess Hathor), originally protecting a small figure (of Menekhibnekau?) standing in front of her. At the same time, examination of the embalmer’s cache adjoining the main shaft of Menekhibnekau continued. In addition to numerous large pottery storage jars and other pottery pieces, some of them inscribed with short texts written in hieratic, fragments of embalming instruments were also obtained. In a summarizing table, hieratic inscriptions discovered so far on the vessels in the tomb of Menekhibnekau at Abusir are listed.